Interventionist and distortionist - Shome, Parthasarathi (2000)
This is an interventionist, distortionist budget, with little bite. The revenue effort is small and the major expenditure proposals look unrealistic. There is something for all, yet little that is incisive. Another opportunity, sadly, has been missed. - Reproduced
Keywords: Budget - India; Budget